Common substitution mutation F348Y of acetylcholinesterase gene contributes to organophosphate and carbamate resistance in Cimex lectularius and C. hemipterus - Komagata, Osamu; Kasai, Shinji; Itokawa, Kentaro; Minagawa, Keiko; Kazuma, Toru; Mizutani, Kiyoshi; Muto, Atsuhiko; Tanikawa, Tsutomu; Adachi, Masaya; Komatsu, Noriyuki; Tomita, Takashi (Insect Biochemistry and Molecular Biology, 2021)
Bed bug control highly depends on insecticides with a limited number of modes of action, especially since the global prevalence of pyrethroid resistance. De facto insecticide options against bed bugs in Japan are acetylcholinesterase inhibitors (AChEis) that consist of organophosphates and carbamates. However, the status of AChEi resistance and the mechanisms involved have not been ascertained. An amino acid substitution mutation, F348Y (or F331Y in standard numbering), occurring at an acyl-binding site of the paralogous AChE gene (p-Ace), was identified among AChEi-resistant colonies of both common and tropical bed bugs (Cimex lectularius and C. hemipterus, respectively). This mutation was genetically associated with propoxur and fenitrothion resistance in F348Y-segregating colonies of C. hemipterus. Inhibition of heterologously expressed C. lectularius p-Ace with insecticides revealed that the sensitivities of F348Y-carrying AChE decreased by orders of 10- to more than 100-fold for diazoxon, carbaryl, fenitroxon, paraoxon, chlorpyrifos-methyl, malaoxon, azamethiphos, methyl-paraoxon, and propoxur. In contrast, the mutant AChE showed a slightly decreased degree of sensitivity for dichlorvos and almost unchanged sensitivity for metoxadiazone. Further studies are needed to ascertain whether the practical efficacies of dichlorvos and metoxadiazone are ensured against F348Y-carrying bed bugs and whether other resistance mechanisms are involved. [Display omitted] •Cimex lectularius resistant to organophosphates and carbamates were found.•F348Y (F331Y in standard numbering) amino acid mutations in p-Ace were identified.•F348Y mutation was also identified in the resistant C. hemipterus.•F348Y contributes to p-Ace low sensitivity for the insecticide activators.•F348Y is an important factor in insecticide resistance in both bed bugs.